A Qualitative Study of Digital Religious Influence: Perspectives from Christian, Hindu, and Muslim Gen Y and Gen Z in Mumbai, India - Clyde Anieldath Missier (Religions)
This study addresses how religious affective content in digital media influences epistemic authority, social imaginaries, and religious beliefs. It draws on data from 64 in-depth interviews with Generation Y and Generation Z individuals with a higher-education background who identified as Christian, Muslim, or Hindu, conducted in Mumbai, India. While influencers are increasingly playing a significant role in the daily lives of the respondents, the impact of family on religious behavior appears to be more substantial than the epistemic sources on social media. In this context, accrued social capital can help individuals develop resilience or resistance to online disinformation, hate speech, and radicalization. Furthermore, while individuals exhibited animosity toward politicians and journalists, they also expressed nationalist attitudes, e.g., a shared Indian identity and common cultural capital, which may serve as ‘superglue’ for living peacefully in the current climate shaped by religious fundamentalist movements. In general, this field study contributes to the ongoing scholarly growth of the interdisciplinary focus of digital religion studies, and particularly on the impact of the social media domain on fundamentalist beliefs.